The Effect of Oil Price Volatility, Board of Directors Characteristics on Firm Performance of Iraq Listed Companies: A Conceptual Framework - Gedi, Firas Farhan; Nayan, Sabri (International Journal of Economics and Financial Issues, 2018)
Economies all over the world need the effective and efficient performance of business units both financial and non-financial firms because they are the engine of economic development of nations. Furthermore, many companies around the world try to improve their performance for the purpose of getting fund from investors in order to expand and to grow. On the other hand, investors need to have confidence that the company is being well managed and will continue to be profitable investments. The poor performance of listed firms around the world has been attributed to ineffective Corporate Governance. Additionally, the performance of Iraq listed firms is discouraging given the declining nature of its price index performance from 2011 to 2015. Besides, the Iraq’s economy is a strong member of OPEC which is an association major oil exporting countries which are oil dependent economies. The adverse effect of oil price volatility can have negative consequences on the Iraqi firms’ performance in spite of strong board’s characteristics while a favorable oil price changes can have the reverse effect. Therefore, the effect of board of directors’ structure on firm performance is among the corporate governance primary mechanism which drawn the attention of many researchers. Despite these, researches have given little attention to the joint effect of oil price volatility on the effect of and board characteristics on firm performance. Therefore, aim of this paper is to propose a framework that will investigate the moderating role joint effect of oil price volatility and board characteristics in influencing firm performance of Iraqi listed companies. It is anticipated that this study and the proposed framework will have wide generalization to economics constrained by weak firm performance that are mostly associated with volatile oil price and weak corporate governance that deteriorates economic development. Keywords: Board of directors, firm performance, government link of the board, oil price volatility. JEL Classifications: G38, M40, M41